Human Bone Marrow Mesenchymal Stem Cells Isolation, Expansion and Identification - Al-Sawalha, Sarah M.; H. Yanzeel, Jabbar; A. Hammadi, Abdul-Majeed (Iraqi Journal of Science, 2023)
The present study aimed to isolate and diagnose mesenchymal stem cells derived from human bone that is the source generating cells that are the best types of treatment for tissue diseases.Cells were isolated from the back bone of the human pelvis, separated using density gradual sedimentation method and then the cells were grown on the culture media RPMI-1640 20% FBS.To detect the purity of cells that have been isolated and have been transplanted immune use the method using CD44 (mesenchymal stem cells marker) CD43, a specific marker for hematopoietic cells Nestin, (the neurons private marker).The present study has shown that mesenchymal cells that have been isolated and expanded in this experiment has reached up 99.7% for the CD44 marker and only 1.1% for the hematopoietic cells marker CD34 and finally was 23.9% for the parameters for the neuronal marker Nestin.